The Effectiveness of the PowerPoint-Based Make A Match Interactive Learning Model for Improving Beginning Reading Skills for Children with Physical Impairment - Intan Aulia; Nurhastuti Nurhastuti; Zulmiyetri Zulmiyetri; Ardisal Ardisal; Retno Triswandari (Universitas Muhammadiyah Enrekang, 2024)
This research aims to improve the initial reading skills of children with physical impairments at SLB Negeri 1 Harau by using the PowerPoint-based Interactive Make A Match learning model. The interactive learning model is a learning approach in which students are active in the teaching and learning process so that students can be fully involved, both physically and mentally. This research uses a quantitative approach with experimental methods, namely Single Subject Research (SSR) and A1-B-A2 Design, and data is analyzed using visual graphs by entering data in graphs which are then analyzed based on conditions A1-B-A2. The results of research using the PowerPoint-based Make A Match Interactive learning model can improve the initial reading skills of children with physical impairments at SLB Negeri 1 Harau.